Food blog: A new wave in the culinary arts setting / Farina Nozakiah Tazijan... [et al.] - Tazijan, Farina Nozakiah; Zulkifli, Fazrul Azmi; Razali, Mohd Azli; Zainool, Noorliza; Mohamed Apandi, Siti Rohimi (Universiti Teknologi MARA, Kedah, 2013)
With the recent advancement of technology, classes are shifting from the traditional teaching to interactive teaching and learning environment. One of the popular ways educators opt for is by blogging. Blog enables students and teachers to post and share their ideas, comments and thoughts. In this research, blogging is introduced to a group of University Technology MARA Penang Culinary degree students in their Food Writing class with the aim to investigate their perceptions towards blogging in the culinary settings and how their perceptions are associated with their engagement in blogging. Students use blog to write their food review and food critique in their food writing class throughout the semester by consistently reporting their reviews and critiques from food sampling that were introduced to them in their culinary visits. Drawing data from gathered interviews and questionnaires, the research reveals the success of academic blogging depends on the participation and motivational aspects from the students, social networks and instructors are the main contributing factors to provide continuous blogging.